Report of the Australian Rotavirus Surveillance Program, 2000/2001 - Masendycz, Paul; Bogdanovic-Sakran, Nada; Kirkwood, Carl; Bishop, Ruth; Barnes, Graeme (Communicable Diseases Intelligence, 2001)
The National Rotavirus Reference Centre together with 15 collaborating laboratories Australia-wide conducted rotavirus surveillance from June 1999. The serotypes of rotaviruses that are responsible for the hospitalisation of children with acute diarrhoea were determined for the period June 2000 to May 2001. We examined 1108 rotavirus specimens using a combination of monoclonal antibody immunoassay, reverse transcription-PCR, and Northern hybridisation. Serotype G1 strains were the most prevalent overall (49.5%), and found in all centres. Serotype G9 rotaviruses, which were first identified in 1997, were second in importance (18.1%). Serotype G2 viruses were next (12.5%), followed by the re-emergence of serotype G4 viruses (9.7%). The findings of this study have implications for vaccine development strategies where protection against serotypes additional to G1-G4 may be required. Commun Dis Intell 2001;25:143-146.